Evaluation of osteoblasts viability, alkaline phosphatase production and collagen secretion in the presence of TiHA - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2004)
Titanium reinforced hydroxyapatite (TiHA), prepared in a 5% and 10% ratio and synterized at 1200degreesC and 1300degreesC, were analysed. 5% TiHA synterized at 1300degreesC showed significant increase in collagen production, when compared to the others TiHA and to control.
Keywords: titanium; collagen; alkaline phosphatase; osteoblast; hydroxyapatite; HYDROXYAPATITE